Green Tea Epigallocatechin-3-Gallate Regulates Autophagy in Male and Female Reproductive Cancer - Hung, Sze Wan; Li, Yiran; Chen, Xiaoyan; Chu, Kai On; Zhao, Yiwei; Liu, Yingyu; Guo, Xi; Man, Gene Chi-Wai; Wang, Chi Chiu (Frontiers in Pharmacology, 2022)
With a rich abundancy of natural polyphenols, green tea has become one of the most popular and healthiest non-alcoholic beverages being consumed worldwide. Epigallocatechin-3-gallate (EGCG) is the predominant catechin found in green tea, which has been shown to promote numerous health benefits, including metabolic regulation, antioxidant, anti-inflammatory and anticancer. Clinical studies have also shown the inhibitory effects of EGCG on cancers of male and female reproductive system, including ovarian, cervical, endometrial, breast, testicular and prostate cancers. Autophagy is a natural, self-degradation process that serves important functions in both tumor suppression and tumor cell survival. Naturally derived products have potential to be an effective and safe alternative in balancing autophagy and maintaining homeostasis during tumor development. Although EGCG has been shown to play critical role in the suppression of multiple cancers, its role as autophagy modulators in cancers of male and female reproductive system remains to be fully discussed. Herein, we aim to provide an overview on the current knowledge of EGCG on targeting autophagy and its related signaling mechanism in the reproductive cancers. Effects of EGCG on regulating autophagy toward the reproductive cancers as a single therapy or co-treatment with others chemotherapies will be reviewed and compared. Additionally, the underlying mechanisms and crosstalk of EGCG between autophagy and other cellular processes, such as reactive oxidative stress, ER stress, angiogenesis, apoptosis, will be summarized. The present review will help to shed light on the significance of green tea as potential therapeutic treatment for reproductive cancers through regulating autophagy.